2020
DOI: 10.1016/j.dsx.2020.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a predictor for a poor prognosis of COVID-19: A systematic review

Abstract: Background and aims: COVID-19 is an emerging pandemic due to droplet infection of 2019-novel coronavirus (2019-nCoV). Due to its rapid transmission and high case-fatality rate, recognition of its risk and prognostic factor is important. Obesity has been associated with impaired immune system, increasing the susceptibility for 2019-nCoV infection. We aimed to study the impact of obesity to the prognosis and disease severity of COVID-19. Methods: A systematic search and handsearching was conducted in four databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
174
4
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(215 citation statements)
references
References 21 publications
14
174
4
23
Order By: Relevance
“…That review found that obesity was associated with the increasing prevalence of hospitalization (average of 20.4%) and greater lethality (average of 20.4%) in the patient with COVID-19 (77). The contribution of obesity to diseases severity and the requirement of advanced medical care in COVID-19 has been also stated in another initial review that only included 3 studies (78). Our study also further added to a meta-analysis that showed obesity is a risk factor for both ICU admission and mechanical ventilation requirement in COVID-19 patients (11).…”
Section: Discussionsupporting
confidence: 56%
“…That review found that obesity was associated with the increasing prevalence of hospitalization (average of 20.4%) and greater lethality (average of 20.4%) in the patient with COVID-19 (77). The contribution of obesity to diseases severity and the requirement of advanced medical care in COVID-19 has been also stated in another initial review that only included 3 studies (78). Our study also further added to a meta-analysis that showed obesity is a risk factor for both ICU admission and mechanical ventilation requirement in COVID-19 patients (11).…”
Section: Discussionsupporting
confidence: 56%
“…A dedicated etiologic study with larger number of cases and in different age groups is warranted to investigate the predictability of this factor. Obesity has been reported as an independent risk and prognostic factor for the disease severity and the requirement of advanced medical care in COVID-19 [ 18 ]. Klang et al concluded that morbid obesity is an independent risk factor for mortality of COVID-19 in hospitalized patients under the age of 50 years [ 19 ], the same age range as our study.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis factors of COVID-19 patients include age, [ 50 , 58 ] sex, [ 50 , 58 ] obesity, [ 59 ] smoking, [ 55 , 60 – 62 ] C-reactive protein (CRP), D-dimer, and lymphocyte count. [ 50 ]…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…[ 63 ] Concerning obesity, it contributes to the increased risk and poorer prognosis of COVID-19. [ 59 ] As for smoking, it is very likely to be related to the negative progression and adverse consequences of COVID-19. [ 55 , 60 – 62 ]…”
Section: Prognostic Factorsmentioning
confidence: 99%